2009
DOI: 10.1061/(asce)0899-1561(2009)21:6(244)
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Simulation of Influence of Frost Damage on Mechanical Properties of Concrete

Abstract: Meso-scale constitutive models of frost-damaged concrete are developed in this study through numerical simulation using a two-dimensional Rigid Body Spring Model (RBSM). The aim of the simulation is to predict the macro behavior of frost-damaged concrete subjected to mechanical loading. The models also clarify the difference in failure behavior of concrete with and without frost damage. Zero strength elements and the concept of meso-scale plastic tensile strain are introduced into the normal RBSM springs to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 10 publications
1
44
0
Order By: Relevance
“…From Fig. 2 (b), ε pa can be also estimated by the residual stiffness (k n (n+1) ) and residual strain (ε pf (n) ) of a certain cycle n, like Hasan's test (Hasan 2004;Ueda 2009). …”
Section: Mechanical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…From Fig. 2 (b), ε pa can be also estimated by the residual stiffness (k n (n+1) ) and residual strain (ε pf (n) ) of a certain cycle n, like Hasan's test (Hasan 2004;Ueda 2009). …”
Section: Mechanical Modelmentioning
confidence: 99%
“…In addition, this discrete model has advantages to show the cracking, which eventually causes failure. Previous researchers have used RBSM to simulate the concrete materials under static loads (Nagai et al 2004), fatigue loads (Matsumoto et al 2008) and also the mechanical properties of frost damaged concrete (Ueda et al 2009). Due to its advantages in modeling of the cracks, the frost damage related durability problems such as moisture transport and chloride migration can be also simulated using RBSM .…”
Section: Introductionmentioning
confidence: 99%
“…The normal spring in Nagai's model is assumed to be- have elastically based on an elastic-fracturing concept, which allows the linear unloading and reloading path passing through the origin. However, based on the experimental fact that there are remaining strains under both compression and tension in macro-scale, Ueda et al (2009) modified the unloading-reloading path (Fig. 4(b)), which is based on an elastoplastic and fracture behavior.…”
Section: Model For Damaged Concretementioning
confidence: 99%
“…For example, Nagai et al (2004Nagai et al ( , 2005 succeeded in simulating the failure mechanism and failure modes of mortar and concrete specimens using both two and three dimensional models. Ueda et al (2009) also proposed a meso-scale constitutive model for frost damaged concrete subjected to mechanical loading. However, there is no constitutive model for frost damage impact itself, for which the failure of material is considered caused by internal freezing.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of internal damage will be cumulated during numbers of FTC and result in gradual degradation in material properties (Hasan et al 2004;Gong et al 2013). As a result, for concrete damaged by FTCs, the static and the fatigue strengths at room temperature will also be reduced (Ueda et al 2009;Hasan et al 2008). During large numbers of FTCs, the additional water supply plays a crucial role in the damage accumulation (Fagerlund 2002 Hasan et al (2004) up to 300 cycles was found to increase in the peak and residual strains, while in the closed test by Sicat et al (2013), the expansive damage stops just after a few cycles.…”
Section: Introductionmentioning
confidence: 99%